Neural Progenitor Cell-Derived Extracellular Vesicles Enhance Blood-Brain Barrier Integrity by NF-κB (Nuclear Factor-κB)-Dependent Regulation of ABCB1 (ATP-Binding Cassette Transporter B1) in Stroke Mice. Issue 3 (17th December 2020) - Zhang, Lin; Graf, Irina; Kuang, Yaoyun; Zheng, Xuan; Haupt, Matteo; Majid, Arshad; Kilic, Ertugrul; Hermann, Dirk M.; Psychogios, Marios-Nikos; Weber, Martin S.; Ochs, Jasmin; Bähr, Mathias; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Extracellular vesicles (EVs) derived from neural progenitor cells enhance poststroke neurological recovery, albeit the underlying mechanisms remain elusive. Since previous research described an enhanced poststroke integrity of the blood-brain barrier (BBB) upon systemic transplantation of neural progenitor cells, we examined if neural progenitor cell-derived EVs affect BBB integrity and which cellular mechanisms are involved in the process. Approach and Results: Using in vitro models of primary brain endothelial cell (EC) cultures as well as co-cultures of brain ECs (ECs) and astrocytes exposed to oxygen glucose deprivation, we examined the effects of EVs or vehicle on microvascular integrity. In vitro data were confirmed using a mouse transient middle cerebral artery occlusion model. Cultured ECs displayed increased ABCB1 (ATP-binding cassette transporter B1) levels when exposed to oxygen glucose deprivation, which was reversed by treatment with EVs. The latter was due to an EV-induced inhibition of the NF-κB (nuclear factor-κB) pathway. Using a BBB co-culture model of ECs and astrocytes exposed to oxygen glucose deprivation, EVs stabilized the BBB and ABCB1 levels without affecting the transcellular electrical resistance of ECs. Likewise, EVs yielded reduced Evans blue extravasation, decreased ABCB1 expression as well as an inhibition of the NF-κB pathway, and downstream matrix metalloproteinase 9 (MMP-9) activity in stroke mice. The EV-induced inhibition of the NF-κB pathway resulted in a poststroke modulation of immune responses. Conclusions: Our findings suggest that EVs enhance poststroke BBB integrity via ABCB1 and MMP-9 regulation, attenuating inflammatory cell recruitment by inhibition of the NF-κB pathway.